Insecurity and Electoral Participation in Southwest and Southeast Nigeria - Adewara, Sunday; Owhe, Robert Goodluck; Mbukanma, Ifeanyi; Yiseyon, Hosu (Journal of Cultural Analysis and Social Change, 2025)
This study examines how insecurity affects voter turnout in the 2023 general elections in Nigeria, with a particular focus on the southwest and southeast regions. Using the Civic Voluntarism Model (CVM), the study highlights how specific types of insecurity, including politically motivated violence in the southwest and ideology-based militia insecurity in the southeast, influenced electoral behavior. Employing a qualitative comparative historical review and using secondary data, the study finds that physical violence and psychological fear largely influenced voter participation. In the southwest, episodic violence by party-affiliated thugs undermined voter turnout, while the southeast experienced persistent intimidation from separatist ideological militias. Both situations deprived participants of resources, motivation, and mobilization, negatively impacting democracy. The study, therefore, recommends region-specific security measures to address security needs and boost voter confidence and turnout.